Etika Bisnis dan Perlindungan Konsumen dalam Algoritma Rekomendasi Marketplace: Studi Kritis Atas Keberpihakan Sistem AI - Suarjana, I Wayan (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
The advancement of artificial intelligence (AI) technology has significantly transformed recommendation systems within digital marketplace platforms. While these algorithms are designed to enhance user efficiency and satisfaction, they may exhibit structural bias favoring certain business actors, particularly those who pay for promotional visibility. This raises critical concerns regarding fairness and consumer protection in digital transactions. This study aims to examine the practice of algorithmic recommendation from the perspective of business ethics and to assess the legal protection of consumers against potential system manipulation. The research employs a normative legal approach with an interdisciplinary critical analysis. The findings indicate that the preferential treatment embedded within algorithmic systems violates core principles of business ethics, such as justice and transparency. Moreover, current legal frameworks, including Indonesia's Consumer Protection Law, have yet to explicitly regulate the use of AI in this context. Therefore, there is an urgent need for adaptive regulatory frameworks that can address the complexities of digital technology, alongside ethical business commitments to ensure fair and accountable recommendation systems.